2021
DOI: 10.25259/sni_769_2021
|View full text |Cite
|
Sign up to set email alerts
|

Spondylodiscitis due to anaerobic bacteria Veillonella parvula: Case report and literature review

Abstract: Background: While pyogenic spondylodiscitis due to Gram-positive aerobic bacteria and its treatment is well known, spondylodiscitis caused by anaerobic Gram-negative pathogen is rare. In particular, the spondylodiscitis caused by Veillonella species is an absolute rarity. Thus no established management recommendations exist. Case Description: A case report of a 79-year-old man with spondylodiscitis caused by Veillonella parvula with intramuscular abscess collection managed conservatively with stand-alone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…4b ). There are many case reports regarding the contribution of Veillonella parvula to various bone diseases, including spondylodiscitis, osteomyelitis and primary sclerosing cholangitis 34 36 . Recent studies have further suggested an association between osteoporosis and these bone dysfunctions.…”
Section: Resultsmentioning
confidence: 99%
“…4b ). There are many case reports regarding the contribution of Veillonella parvula to various bone diseases, including spondylodiscitis, osteomyelitis and primary sclerosing cholangitis 34 36 . Recent studies have further suggested an association between osteoporosis and these bone dysfunctions.…”
Section: Resultsmentioning
confidence: 99%